2017
DOI: 10.1016/j.ajem.2017.03.051
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with hospital admission after an emergency department treat and release visit for older adults with injuries

Abstract: Introduction Emergency Department (ED) visits for injury often precede hospital admissions in older adults, but risk factors for these admissions are poorly characterized. We sought to determine the incidence and risk factors for hospitalization shortly following discharge home from an ED visit for traumatic injury in older adults. We hypothesized higher risk for admission in those with increased age, discharged home after falls, with increased comorbidity burden, and who live in poor neighborhoods. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At the same time, marginalized, underserved, low socioeconomic status (SES) and racial/ethnic minority populations who are more likely to have multiple CMCs are at an increased risk of hospitalization and ED visits [6]. Living in economically disadvantaged areas (low SES neighborhoods) is also associated with increased risk of hospitalization and with higher likelihood of visiting the ED [7].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, marginalized, underserved, low socioeconomic status (SES) and racial/ethnic minority populations who are more likely to have multiple CMCs are at an increased risk of hospitalization and ED visits [6]. Living in economically disadvantaged areas (low SES neighborhoods) is also associated with increased risk of hospitalization and with higher likelihood of visiting the ED [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our discovery that 73% of subsequent admissions stem from a wide range of non-injury-related medical issues is a key finding in our study, and it confirms our initial hypothesis: The event (often a ground-level fall) that resulted in the injury might indicate an undetected disease. A recent study on community-dwelling older adults in the USA who were treated for injuries and released from the ED showed a readmission rate of 7.9% within 30 days, hereof 64.5% due to non-trauma [ 17 ]. This highlights that a traumatic event such as a fall can indicate an incipient acute illness such as an infection or a deterioration of chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…pneumonia or delirium. A study showed that 8% of community-dwelling older adults treated for a traumatic injury (69% fall-related) and released from the ED experienced an in-hospital admission within the next 30 days, hereof 64.5% due to non-traumatic illnesses such as infections and congestive heart failure [ 17 ]. It is very difficult to distinguish whether the acute illness arose before or as a consequence of the fall that resulted in an ED visit.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults often experience adverse events after an ED visit [9]. Low neighborhood income and high comorbidity status are contributing risk factors for in-patient hospitalization within 30 days of an ED visit among older adults [10].…”
Section: Introductionmentioning
confidence: 99%